2017
DOI: 10.1177/2309499017718909
|View full text |Cite
|
Sign up to set email alerts
|

Sequentially annealed highly cross-linked polyethylene reduced in vivo wear particle generation in total knee arthroplasty

Abstract: The sequentially annealed HXLPE reduced the in vivo polyethylene wear particles by 58% compared with conventional polyethylene without the significant change of particle size and shape.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…For each outcome, the analysis did not show any significant publication bias effect. No significant heterogeneity was observed in the statistical analysis results for each outcome analysed in the included studies [ 16 , 23 , 25 , 26 , 29 , 42 ]. There was no statistically significant difference found regarding the superiority of HXLPE over CPE for all outcomes assessed above ( p > 0.05) (Figs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For each outcome, the analysis did not show any significant publication bias effect. No significant heterogeneity was observed in the statistical analysis results for each outcome analysed in the included studies [ 16 , 23 , 25 , 26 , 29 , 42 ]. There was no statistically significant difference found regarding the superiority of HXLPE over CPE for all outcomes assessed above ( p > 0.05) (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Kindsfater et al [ 26 ] observed similar Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) [ 13 ] values in the postoperative period between the two types of liners compared. Minoda et al [ 42 ] did not find a benefit in the use of HXLPE over CPE in either range of motion (ROM) or University of California Los Angeles (UCLA) activity score [ 45 ] in the postoperative period. Lachiewicz et al [ 29 ], in their study, found similar results comparing the lower extremity activity score (LEAS) [ 55 ] in the two polyethylene groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meneghini et al [ 11 ] reported no radiographic osteolysis or mechanical failure of the tibial polyethylene at 5-year follow-up. Minoda et al [ 12 ] showed a 58% reduction of the number of in vivo X3® wear particles compared to conventional PE in TKA.…”
Section: Introductionmentioning
confidence: 99%